Examining language anxiety and academic success of Saudi international students in U.S. colleges - Alkhaldi, Shahinaz; Bista, Krishna (Journal of International Students, 2025)
This study examines the relationship between academic performance (GPA), Foreign Language Classroom Anxiety (FLCA), and English proficiency (IELTS scores) among Saudi international students in the United States while considering demographic factors such as gender, age, college major, and length of U.S. residency. Data from 551 students, collected via an online survey, reveal a moderate negative relationship between FLCA and GPA but no significant correlation between IELTS scores and GPA. Regression analysis identifies key predictors of academic performance, including low FLCA levels, college majors, and earning a master’s degree in English-speaking countries. The findings emphasize the importance of addressing language anxiety and demographic diversity to enhance academic success for Saudi students in U.S. colleges.